AN EVALUATION OF CONSTITUTIONAL CONSTRAINTS ON CAPITAL TAXATION. (10th August 2016) - Domínguez, Begoña; Feng, Zhigang
Abstract : This paper investigates the desirability of constitutional constraints on capital taxation in an environment without government debt and where benevolent governments have limited commitment. In our setup, governments can choose proportional capital and labor income taxes subject to the constitutional constraint but cannot commit to an actual path of taxes. First, we explore a form of constitutional constraint: a constant cap on capital tax rates. In our quantitative exercise, we show that a three percent cap on capital taxes provides the highest welfare at the worst sustainable equilibrium. However, such a cap decreases welfare at the best sustainable equilibrium (both because it constrains feasibility and because it tightens the incentive compatibility constraint). Second, we identify a form of constitutional constraint that can improve all sustainable equilibria. That constraint features a cap on capital taxes that increases with the level of capital.